(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Springs in the Himalayan region are significant for domestic, agricultural, and ecological needs, yet they face declining flows, seasonal variability, and potential contamination from urbanisation, tourism, and climate change. Limited studies exist on water quality in the Middle Himalayas. The present study focuses on assessing water quality in springs of Banjar Block, Kullu Valley, Himachal Pradesh, where high relief and monsoonal turbidity make surface water unreliable, emphasising the reliance on springs and Bawdis. This study aims to assess the suitability of these sources for domestic use by evaluating their physical, chemical, and bacteriological parameters. Nineteen water samples have been collected from perennial springs using purposive sampling and analysed in government laboratories for 11 key parameters following the BIS IS 10500 methods. The Weighted Arithmetic Water Quality Index (WAWQI) was computed, assigning weights based on health and usability priorities. The study highlights that no E. coli or total coliforms were found, indicating that the water quality is excellent at all springs. The average values of the study reflect a TDS of 153.03 mg/L, total hardness of 68.29 mg/L, turbidity of 0.22 NTU, and a pH of 7.6. The results of all parameters fall within the permissible limits of the BIS standard. It is evident from the study that the water quality index, ranging from 10.81 to 20.18, is identified as “Excellent” and these pristine, untreated waters support safe domestic use for mountain people. However, in the face of mounting challenges, community conservation and spring shed management are necessary for sustainable Himalayan development.